A journey into navigating religious diversity in Türkiye through the eyes of two school principals - Kuyurtar, Dilan; Tabancali, Erkan (SAGE PUBLICATIONS LTD, 2026)
This study aimed to explore how school principals manage religious diversity in schools with teachers of different religious beliefs. Using a qualitative approach, data were collected through face-to-face interviews with two principals selected based on their experience managing religious diversity. The interviews were analyzed using narrative thematic analysis, revealing three key themes: embracing diversity, conflict resolution, and inclusive leadership. In the embracing diversity theme, principals emphasize recognizing and valuing differences among teachers. The conflict resolution theme focuses on strategies for resolving disputes related to religious beliefs in a fair and constructive way. The inclusive leadership theme highlights leadership practices where principals ensure all individuals feel represented and valued, promoting equality and collaboration. The findings show that principals adopt an integration and learning approach to managing diversity. To create an inclusive school culture, the study suggests implementing legal regulations to address individual religious needs, such as flexible holiday schedules and prayer spaces. It also recommends expanding leadership training programs for principals to improve skills in conflict resolution, inclusion, and managing religious diversity. These programs can help principals foster respectful dialogues among teachers of different beliefs.
Keywords: diversity management; diversity at school; narrative analysis; religious diversity; inclusivity; PERSPECTIVES; LEADERSHIP; MANAGEMENT; EDUCATION; Education & Educational Research